2002
DOI: 10.1152/ajplung.00347.2001
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of ornithine decarboxylase and polyamine import by hypoxia in pulmonary artery endothelial cells

Abstract: In rat lung and cultured lung vascular cells, hypoxia decreases ornithine decarboxylase (ODC) activity and increases polyamine import. In this study, we used rat cultured pulmonary artery endothelial cells to explore the mechanism of hypoxia-induced reduction in ODC activity and determined whether this event was functionally related to the increase in polyamine import. Two strategies known to suppress proteasome-mediated ODC degradation, lactacystin treatment and use of cells expressing a truncated ODC incapab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 33 publications
0
29
0
1
Order By: Relevance
“…Initial studies on apoptosis in thymocytes observed polyamine depletion as an unsuspected finding and hypothesized that polyamine depletion contributed to the activation of apoptosis (25). Agmatine depletes intracellular polyamine levels to suppress growth (4,16,22,29,46,59,68). Supplementation with the polyamine putrescine attenuates this effect (22,33,59).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Initial studies on apoptosis in thymocytes observed polyamine depletion as an unsuspected finding and hypothesized that polyamine depletion contributed to the activation of apoptosis (25). Agmatine depletes intracellular polyamine levels to suppress growth (4,16,22,29,46,59,68). Supplementation with the polyamine putrescine attenuates this effect (22,33,59).…”
Section: Discussionmentioning
confidence: 99%
“…Ras/3T3 cells were collected and lysed [lysis buffer contained 1% Triton X-100, 0.5% deoxycholic acid, 1 mM EDTA, 0.1% SDS, 4 mM NaF, complete protease cocktail (Roche Molecular Biochemicals, Mannheim, Germany), 0.7 g/ml pepstatin, and 1 mM NaVO 4 in PBS]. Lysates at 50 g/lane were resolved on 12% NuPAGE gels in MOPS buffer (Invitrogen, Carlsbad, CA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One possibility is that plants are equipped with two alternative pathways for polyamine biosynthesis that function independently in the plant defense network. Another possibility is that Arg decarboxylase regulates polyamine levels in a similar manner as in mammalian cells, in which agmatine, a product of Arg decarboxylase, has been shown to exert effects by inducing an antizyme for ODC (Babal et al, 2001). …”
Section: Alternative Pathways For Hydrogen Peroxide Productionmentioning
confidence: 99%
“…Arginine decarboxylase activity is associated with mitochondrial membranes and is most prevalent in kidney, liver, and brain (Lortie et al, 1996). Agmatine is present in plasma and is widely but unevenly distributed in mammalian tissue (Raasch et al, 1995).There is evidence that agmatine acts as an antiproliferative molecule through induction of the protein antizyme (Satriano et al, 1998;Babal et al, 2001). Antizyme inhibits ornithine decarboxylase and hence polyamine (putrescine, spermine, and spermidine) biosynthesis.…”
mentioning
confidence: 99%